STUNTING RISK ; DESCRIPTION OF MOTHER'S KNOWLEDGE LEVELS ABOUT NUTRITION FOR TOLLS IN BELIMBING PADANG HEALTH CENTER - Aulia Asman; An Aulingga Asman (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2021)
Based on the report from the Padang City Health Office, the health service sector reported the nutritional status of toddlers in the city of Padang, among others, the poor nutritional status of 96 toddlers (3.05%) and undernutrition status of 385 toddlers (12.22%), and normal nutrition 2,622 toddlers (83 ,24%) and over nutrition 47 children under five (1,49%). The highest malnutrition status was found in Belimbing Health Center, namely 10 people (13%) and undernourished as many as 54 people (69.2%) of the total number of toddlers as many as 78 people. The purpose of this study was to describe the level of knowledge of mothers about nutrition in children under five at the Belimbing Health Center. This type of research is descriptive which has been carried out at the Belimbing Padang Health Center. The population was all mothers of children under five who visited the Belimbing Padang Health Center totaling 78 people and the sample was taken by a total sampling of 78 people, at the time of the study using a questionnaire by means of a questionnaire. Then the data were analyzed univariately. The results showed (59.0%) mothers had low knowledge about nutrition, (51.3%) mothers had low knowledge about types of nutritious food, (59.0%) mothers had low knowledge about how to process nutritious food, (60.3%) ) mothers have low knowledge about overcoming nutritional problems and (35.9%) mothers have low knowledge about signs of adequate nutrition at the Belimbing Padang Health Center. Based on the results of the study, it can be concluded that the level of mother's knowledge about nutrition for toddlers is still low, so it is hoped that health service agencies such as puskesmas, sub-health centers, posyandu, cadres are expected to be able to reactivate health counseling or promotion activities in the community by going directly to residents' homes, especially on mothers who have less knowledge about toddler nutrition.